CHARACTERISTICS AND RISK FACTORS FOR SUICIDAL BEHAVIOR AMONG MEN AND WOMEN WITH PSYCHIATRIC DISORDERS - Nadja Cristiane Lappann Botti; Luiza Cantão; Aline Conceição Silva; Thais Gonçalves Dias; Livian Carrilho Menezes; Ramon Azevedo Silva de Castro (Universidade Federal do Paraná, 2018)
Objective: to identify characteristics of suicidal behavior and risk factors among men and women with psychiatric disorders. Method: quantitative study of 410 medical records of psychiatric patients receiving treatment, from 1997 to 2014, with descriptive and inferential analysis of the service's medical records. Undertaken between April - December 2015, in a Psychosocial Care Center in Divinópolis, in the Brazilian state of Minas Gerais. Result:the higher frequency of suicidal behavior among women was, also, the most frequent reason for admission for treatment in the service. Self-poisoning was more common among the women, while hanging was more common among the men. Upon admission for suicidal behavior, the women's characteristics were mood disorders, and the men's were disorders due to the use of psychoactive substances. Suicidal behavior in men was associated with family history of suicide, while among women, it was associated with physical or sexual abuse. Conclusion:Evidence was found for specific characteristics of suicidal behavior among psychiatric patients receiving treatment in relation to gender.